Metformin for treatment of antipsychotic-induced weight gain in a South Asian population with schizophrenia or schizoaffective disorder: A double blind, randomized, placebo controlled study - Hanwella, Raveen; De Silva, V.A.; Dayabandara, M.; Wijesundara, H.; Henegama, T.; Gunewardena, H.; Suraweera, C. (SAGE, 2015)
Background: Antipsychotic-induced weight gain causes serious health problems. We investigated the efficacy and safety of metformin in treating antipsychotic-induced weight gain in South Asian patients. Methods: Sixty six adult patients with schizophrenia or schizoaffective disorder treated, with atypical antipsychotics, and who had increased by more than 10% their pre treatment body weight, were randomly assigned to receive metformin or placebo in a double-blind study. Patients received usual treatment and metformin 500 mg or placebo twice daily for 24 weeks. The primary outcome measure was change in body weight from baseline to week 24. Linear mixed models were used in the analysis. Results: Mean change in body weight in the metformin group was -1.56 kg (95% CI=-3.06 to -0.05) and 1.0 kg (95% CI=0.03-1.97) in the placebo group. Between-group difference was 2.56 kg. At 24 weeks the between-group difference showed significant time-by-treatment interaction (F=3.23, p=0.004). Between-group difference in BMI showed significant time-by-treatment interaction (F=3.41 p=0.03). There was no significant difference in waist-hip ratio or fasting blood sugar. Conclusions: Metformin is effective in reducing weight in South Asian patients with schizophrenia or schizoaffective disorder who had increased their body by more than 10% after treatment with atypical antipsychotics.
Keywords: Schizophrenia; Sri Lanka; antipsychotics; metformin; weight gain